Common variants in the SLCO1B3 locus are associated with bilirubin levels and unconjugated hyperbilirubinemia - Sanna, Serena (Oxford University Press, 2009)
Bilirubin, resulting largely from the turnover of hemoglobin, is found in the plasma in two main forms: unconjugated or conjugated with glucuronic acid. Unconjugated bilirubin is transported into hepatocytes. There, it is glucuronidated by UGT1A1 and secreted into the bile canaliculi. We report a genome wide association scan in 4300 Sardinian individuals for total serum bilirubin levels. In addition to the two known loci previously involved in the regulation of bilirubin levels, UGT1A1 (P = 6.2 × 10(−62)) and G6PD (P = 2.5 × 10(−8)), we observed a strong association on chromosome 12 within the SLCO1B3 gene (P = 3.9 × 10(−9)). Our findings were replicated in an independent sample of 1860 Sardinians and in 832 subjects from the Old Order Amish (combined P < 5 × 10(−14)). We also show that SLC01B3 variants contribute to idiopathic mild unconjugated hyperbilirubinemia. Thus, SLC01B3 appears to be involved in the regulation of serum bilirubin levels in healthy individuals and in some bilirubin-related disorders that are only partially explained by other known gene variants.